Fracture of the extensor process of the distal phalanx in a bull and a cow. Issue 1 (11th July 2013) - Taguchi, K.; Nakamura, S.; Hyakutake, K.
Abstract : Two cases of extensor process fracture of the distal phalanx in the forelimb in a Holstein bull and a lactating Holstein cow are described. Each animal showed acute onset of severe lameness with a gait characterised by lengthening of the cranial phase of the step in order to place more weight on the heel. Mild swelling and a localised pain response upon application of deep pressure above the coronet were also observed. A definitive diagnosis was made by radiography with complementary ultrasonography, which provided the best definition of the fracture fragment over the dorsal aspect of the distal interphalangeal joint. Applying a wooden block to a sound claw for three weeks was curative and provided a good prognosis in both cases.